So I married an axe murderer [videorecording (DVD)] - Schlamme, Thomas; Myers, Mike, 1963-; Travis, Nancy, 1961-; LaPaglia, Anthony (Columbia TriStar Home Video, 1999)
A wedlock-shy coffee house poet finally meets the perfect woman. There's one little problem--he's convinced she's an axe murderer.